The role of oral language skills in reading and listening comprehension of text: a comparison of monolingual (L1) and bilingual (L2) speakers of English language. (23rd August 2012) - Babayiğit, Selma; Kendeou, Panayiota
<x xml:space="preserve">Abstract</x> The study examined the role of oral language skills in reading comprehension and listening comprehension levels of 125 monolingual (L1) and bilingual (L2) English‐speaking learners (M = 121.5 months, SD = 4.65) in England. All testing was conducted in English. The L1 learners outperformed their L2 peers on the measures of oral language and text comprehension, but the two groups performed at comparable levels on word‐reading accuracy and speed. Oral language, indexed by vocabulary and morphosyntactic skills, emerged as the most powerful unique predictor of both reading and listening comprehension levels. Although there was a tendency of oral language to be more strongly related to L2 reading comprehension, its relationship with listening comprehension was comparable across the two language groups. Finally, individual differences in oral language skills emerged as the primary factor that explained the language group differences in text comprehension levels. Educational implications of these findings were discussed.